2003
DOI: 10.1034/j.1600-6143.2003.30113.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Humoral Rejection in Hepatitis C‐Infected Renal Transplant Recipients Receiving Antiviral Therapy

Abstract: The use of interferon-alpha (IFN) in hepatitis C (HCV)-infected renal recipients has been associated with acute rejection and graft loss. We reviewed our recent experience in HCV (π) renal recipients treated with antiviral therapy for biopsy proven chronic hepatitis C. Twelve HCV (π) recipients who recently received antiviral therapy were analyzed. Post-treatment sera were tested for donor-specific human leukocyte antigen (HLA) antibodies (DSA). Within 6 months of initiating antiviral therapy, two of 12 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 19 publications
1
86
0
2
Order By: Relevance
“…IFN treatment of HCV infection carries a risk for graft rejection in renal transplant recipients and such use needs to be very carefully evaluated (186,194). This observation has stimulated studies of lower-dose IFN-␣ (1 ϫ 10 units subcutaneously three times/wk) plus ribavirin (600 mg/d).…”
Section: Hcvmentioning
confidence: 99%
“…IFN treatment of HCV infection carries a risk for graft rejection in renal transplant recipients and such use needs to be very carefully evaluated (186,194). This observation has stimulated studies of lower-dose IFN-␣ (1 ϫ 10 units subcutaneously three times/wk) plus ribavirin (600 mg/d).…”
Section: Hcvmentioning
confidence: 99%
“…In renal transplant recipients with high HCV load, good effectiveness was observed when combination therapy was attempted. However, 2 of 11 patients experienced acute renal failure and graft loss (14). Other studies have demonstrated good effectiveness of IFN therapy when used in hemodialysis patients with chronic hepatitis C (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have investigated the utility of IFN therapy for chronic hepatitis C in renal transplant recipients (Table 2) (3,(6)(7)(8)(9)(10)(11)(12)(13)(14). However, only a few of these reports studied the response in terms of HCV viral load and the response of individual HCV genotypes to therapy (7,13,14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations